Stakeholders’ Decision Making and Sustainability of Potato Projects In Rubanda, Uganda - Agaba, Moses; Turyasingura, John Bosco; Byarugaba, Arinaitwe Julius; Atukwase, Jasper; Alice, Ngele Mwazuna (Asean International Journal of Business, 2026)
With a focus on potato projects in the Rubanda district, this study aimed to investigate how stakeholder decision-making affects the sustainability of donor-funded agricultural projects in Uganda. A cross-sectional survey design was used in the study. A total of 139 respondents' data was gathered, and both quantitative and qualitative analysis were performed. Frequency tables were used to display the data because descriptive analysis involved describing a single variable and its characteristics. A Pearson correlation matrix was used to determine the relationships between the dependent variable and the predictor variables at the bivariate level. To fit the data, a linear regression model was employed. Regression model research results indicate that stakeholders' decisions regarding potato projects have an impact on project sustainability (R=829). The primary finding of this study is that decisions have an impact on the sustainability of potato projects in the district of Rubanda. Therefore, if the sustainability of potato projects in Rubanda district is to be achieved, the study suggests that project managers and project implementers should focus more on stakeholder decision making.